Unpacking 'Gender' in India's Joint Forest Management Program: Lessons from two Indian states - Elias, Marlène (Bioversity International, 2017)
Presented by Marlene Elias (Bioversity International), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.